Effects of phosvitin phosphopeptide-Ca complex prepared by efficient enzymatic hydrolysis on calcium absorption and bone deposition of mice - Mengdie Zhao; Dong Uk Ahn; Songming Li; Wei Liu; Shengwei Yi; Xi Huang (Food Science and Human Wellness)
Phosvitin (PV) was treated with high-temperature, mild pressure (HTMP), and enzyme combination, and then phosvitin phosphopeptides-calcium (PPP-Ca) complexes were prepared. The low-calcium specific pathogen free-Kunming (SPF-KM) mice were used to determine the effect of PPP-Ca complexes on intestinal calcium absorption and their utilization for bone formation. The serum calcium content was the highest with the HTMP-Enz-PPP-Ca treatment (2.19 mmol/L), and it significantly down-regulated the abnormal elevation of serum alkaline phosphatase (AKP) caused by calcium deficiency. The low-calcium control group had the lowest calcium deposited to the femur (80.41 mg/g) and the lowest femur bone mineral density (BMD) (0.17 g/cm3), while HTMP-Enz-PPP-Ca significantly improved bone calcium content (94.33 mg/g) and BMD (0.29 g/cm3). The micro-computed tomography (MCT) images showed that the femur with the normal control, PV-Ca, and HTMP-Enz-PPP-Ca treatments had a more compact, complete, and thicker trabecular network than the low-calcium and CaCl2 treatments. These results indicated that the organic calcium (HTMP-Enz-PPP-Ca) promoted calcium absorption and bone deposition, and the effect of HTMP-Enz-PPP-Ca was better than the inorganic CaCl2.